PEMBUATAN PETA SITUASI DUSUN BABADAN, DESA BELUK, KECAMATAN BAYAT, KABUPATEN KLATEN, PROPINSI JAWA TENGAH - , SALISA BANATI HASANAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final report is the result of field work (PKL) report which describes the measurement and mapping to obtain a picture of the earth surface information. This picture of the Earth's surface by presented on a flat surface in map. The method used in the measurement is direct mapping method on the earth surface (terrestrial). The data obtained from measurements using a measuring instrument and then performed the calculating and plotting. The results of the measurement and mapping is situation map by using scale of 1: 500 at location Babadan hamlet, Beluk village, Bayat sub-district, Klaten district, Central Java province.